HYPNOBIRTHING: A SYSTEMATIC REVIEW OF RELAXATION TECHNIQUES IN REDUCING PRENATAL ANXIETY - Sari, Yona Wia Sartika; Lestari, Risva Aprina Fitri; Pratiwi, Dessy; Nafilata, Ikrimah (Lembaga Penelitian dan Terapan untuk Kesehatan Jiwa (Lenterakaji), 2025)
Background: Anxiety during pregnancy can worsen the health of both mother and fetus if not treated appropriately. Purpose: This study aims to analyze the benefits of hypnobirthing in reducing anxiety in pregnant women. Methods: This study used a systematic review design using the PICO (Population, Intervention, Comparison, Outcome) framework. The search strategy was conducted through electronic databases including PubMed, ScienceDirect, and Google Scholar, with a focus on articles published in the last five years (2021–2025). Keywords used in searches include